Kajian Perilaku Penggunaan Jamban pada Rumah Tangga Desa Webetun Kecamatan Rinhat Kabupaten Malaka - Yulia Dasilva Luruk; Afrona E.L.Takaeb; Petrus Romeo (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
A healthy latrine is one of the essential sanitation facilities aimed at maintaining environmental health and improving public health in general. This research was conducted because the use of healthy latrines in Webetun Village remains low, where defecating in the forest has become a common practice among the community. This habit triggers the emergence of diseases such as diarrhea, malnutrition, undernutrition, dengue fever, and respiratory infections. This study aims to examine the behavior of latrine use in households in Webetun Village, Rinhat Subdistrict, Malaka Regency. This research uses a quantitative approach with a cross-sectional design. The study involved 66 housewives who owned healthy latrines, selected through simple random sampling. Data analysis was conducted using the chi-square test. The results showed that variables such as latrine ownership (p=0.000) and water availability (p=0.000) were significantly associated with latrine use, while knowledge (p=0.681), attitude (p=0.588), actions (p=0.007), community leader support (p=0.081), and health worker support (p=0.069) were not significantly associated with latrine use. The findings revealed that water availability significantly influences latrine use. The availability of water facilitates family members in utilizing latrine facilities for activities such as flushing and maintaining cleanliness. Water availability also contributes to user comfort in maintaining latrine hygiene. Conversely, water scarcity hinders optimal latrine use by family members, potentially reducing utilization levels. The study findings also identified a correlation between latrine ownership and its use. Families are considered critical factors in shaping individual health behavior. The relationship between proper latrine ownership and usage behavior can be seen through the role of education in increasing awareness levels for adopting a healthy and clean lifestyle.